Aripiprazole/Sertraline Combination: Clinical and Cost‐Effectiveness in Comparison With Quetiapine for the Treatment of Bipolar Depression (ASCEnD Trial)—Protocol for a Nested Qualitative Study - Isobel Hoppe; Stuart Watson; Caroline Kemp; Fiona Turnbull; Firoza Davies; John Gibson; Lumbini Azim; Lauren Wall; Niraj Ahuja; Sarah Al‐Ashmori; Sally Keys; Thomas Kabir; et al. (Health Expectations)
ABSTRACT Introduction Bipolar disorder is a recurrent mental health disorder with a prevalence rate of 1.4%. On average, there can be a delay of 9.5 years from the initial presentation of symptoms to a confirmed diagnosis. Individuals living with bipolar disorder have a reduced life expectancy. There is limited evidence regarding the effectiveness of antidepressants in treating bipolar disorder. The ASCEnD clinical trial will test the clinical and cost‐effectiveness of the aripiprazole/sertraline combination in comparison with quetiapine for the treatment of bipolar depression (individuals who suffer from depressive episodes in bipolar disorder) and will include a nested qualitative study. Methods The qualitative study will use semi‐structured interviews to explore pilot trial participants' and clinicians' perspectives on recruitment procedures, the acceptability of the intervention, the management of bipolar disorder and attitudes to medication combinations. Conclusion Findings will inform recruitment strategies and optimise training for the participating sites in the ASCEnD full trial. They will also help to illuminate the lived experience of people with bipolar disorder and the clinicians who work with people with bipolar disorder. The discussion will explore perspectives on the delay in diagnosis, having a diagnosis, the impact of living with bipolar disorder and attitudes to treatment, including drug combinations. Patient or Public Contribution A Lived Experience Advisory Panel (LEAP) has been convened with the support of the McPin Foundation, which will contribute to the ASCEnD trial and its nested qualitative study to provide input on the design and delivery of the trial and qualitative study, analysis of qualitative data and dissemination of findings.